Origins of the North Korean garrison state : the People's Army and the Korean War - Kim, Youngjun (Cold War history, 2018)
"This book investigates the origins of the North Korean garrison state by examining the development of the Korean People's Army and the legacies of the Korean War in political, military, social and cultural contexts. Despite its significance, there are very few books on the Korean People's Army with North Korean primary sources being difficult to access. This book, however, draws on North Korean documents and North Korean veterans' testimonies, and demonstrates how the Korean People's Army and the Korean War shaped North Korea into a closed, militarized and xenophobic garrison state and made North Korea seek Juche (Self Reliance) ideology and weapons of mass destruction. This book maintains that the youth and lower classes in North Korea considered the Korean People's Army as a positive opportunity for upward social mobility. As a result, the North Korean regime secured its legitimacy by establishing a new class of social elites wherein they offered career advancements for persons who had little standing and few opportunities under the preceding Japanese dominated regime. These new elites from poor working and peasant families became the core supporters of the North Korean regime today. In addition, this book argues that, in the aftermath of the Korean War, a culture of victimization was established among North Koreans which allowed Kim Il Sung to use this culture of fear to build and maintain the garrison state. Thus, this work illustrates how the North Korean regime has garnered popular support for the continuation of a militarized state, despite the great hardships the people are suffering. This book will be of much interest to students of North Korea, the Korean War, Asian politics, Cold War Studies, military and strategic studies, and international history."...Provided by publisher